'That brotherhood may prevail': International House Brisbane, race and the humanitarian ethic in Cold War Australia. Issue 4 (1st October 2020) - Piccini, Jon
Abstract: International House opened its doors at the University of Queensland in early 1965 to an initial intake of some 66 residents, split between Australians and students from all over the Asia-Pacific and beyond. Based on college and governmental records, this article makes two arguments. Firstly, that the 'everyday humanitarians' in civil society organisations like Rotary International who championed International House at once critiqued and upheld colonial-era ideas towards Australia's near neighbours. Secondly, that the students whom the college housed sat unsteadily between the two poles of humanitarian goodwill and developmental assistance that they were forced to inhabit, and indeed often rebelled against. In so doing, this article positions International House at the nexus of numerous discourses and practices associated with the Cold War and Australia's geo-political position which muddied boundaries between altruistic assistance and politicised aid.